Measurement of instantaneous power during the vertical jump. - Gaitán González, M. J.; González Camarena, R.; Carrasco Sosa, S.; Yañez Suárez, O. (Revista Mexicana de Ingenieria Biomedica, 1991)
A method of measuring the instantaneous maximum power developed during the vertical jump is proposed, based on the analysis of the instantaneous vertical displacement of the center of mass, calculated from the angular movements of the joints of the hip, knee, ankle and fingers, and their respective interarticular lengths. An aluminum skeleton with four electrogoniometers, whose signals were processed by computers, was fixed to the outer side of the right lower limb. Six subjects were studied, obtaining maximum instantaneous powers of extension (normalized to the weight of the subject) between 23.0 W / Kg. The kinematic and dynamic patterns obtained are like those reported for the force platform. The described electrogonometric method is a good alternative to the platform with a much higher biomechanical analysis potential.